2012
DOI: 10.1074/jbc.m112.345728
|View full text |Cite
|
Sign up to set email alerts
|

High Motility of Triple-negative Breast Cancer Cells Is Due to Repression of Plakoglobin Gene by Metastasis Modulator Protein SLUG

Abstract: Background: High motility of aggressive breast cancer cells is associated with high SLUG and low plakoglobin levels. Results: SLUG binds to plakoglobin gene promoter and represses its expression. Conclusion: SLUG-induced increase in breast cancer cell motility is due to repression of plakoglobin by SLUG. Significance: Management of SLUG level should diminish the motility and thus aggressiveness in breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 47 publications
(122 reference statements)
8
37
0
Order By: Relevance
“…38 These findings confirm previous studies demonstrating the relevance of plakoglobin expression for metastases in breast and lung carcinomas. [39][40][41] ARE CTCS CAPABLE OF INITIATING METASTASES? CTC capturing systems revealed that aggressive tumors release thousands of cancer cells into the circulation each day, 42-44 yet most patients develop only few metastases, suggesting that metastasis is a highly inefficient process.…”
Section: Active or Passive Entry Of Ctcs Into The Circulationmentioning
confidence: 99%
“…38 These findings confirm previous studies demonstrating the relevance of plakoglobin expression for metastases in breast and lung carcinomas. [39][40][41] ARE CTCS CAPABLE OF INITIATING METASTASES? CTC capturing systems revealed that aggressive tumors release thousands of cancer cells into the circulation each day, 42-44 yet most patients develop only few metastases, suggesting that metastasis is a highly inefficient process.…”
Section: Active or Passive Entry Of Ctcs Into The Circulationmentioning
confidence: 99%
“…Suppression of PKC-a or PKC-d isoforms increases Dsg3 expression, whereas suppression of PKC-d and PKC-1 isoforms either decreases or increases Dsg1 levels, respectively (Szegedi et al 2009 (Roemer 2012) and p63 has been shown by chromatin immunoprecipitation (ChIP) to bind and activate Dsg1, Dsc3, and Dp promoters (Ferone et al 2013;Johnson et al 2014). Rho-mediated changes in the actin cytoskeleton lead to changes in Srf-dependent transcription (Miralles et al 2003) and Srf controls the expression of Pkp2 and Dsg1, which in turn drives a program of terminal differentiation (Leitner et al 2011;Dubash et al 2013), The Wnt-regulated TCF/Lef transcription complex has been implicated in regulation of Dsg4, Dsc2, Dsc3, and Pg expression but direct binding of these transcription factors to desmosomal component promoters has only been shown in a few instances (Table 1) (Bazzi et al 2009;Bailey et al 2012;Tokonzaba et al 2013). Pg itself complexes with TCF/ Lef-1 to regulate the balance of Dsc2 and Dsc3 expression (Tokonzaba et al 2013).…”
Section: Transcriptional Regulation Of Desmosomal Componentsmentioning
confidence: 99%
“…In contrast, plakoglobin has often been associated with tumor/metastasis suppressor activity, although the mechanisms underlying this activity remain unclear. A number of studies have suggested that plakoglobin decreases cell proliferation, migration and invasion and induces apoptosis (Simcha et al, 1996;Parker et al, 1998;Pantel et al, 1998;Charpentier et al, 2000;Winn et al, 2002;Rieger-Christ et al, 2005;Yin et al, 2005;Dusek et al, 2007;Kanazawa et al, 2008;Närkiö-Mäkelä et al, 2009;Todorović et al, 2010;Aktary et al, 2010;Aktary and Pasdar, 2012;Bailey et al, 2012;Holen et al, 2012;Franzen et al, 2012;Lam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%